2016
DOI: 10.1016/j.neurol.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution, a rising environmental risk factor for cognition, neuroinflammation and neurodegeneration: The clinical impact on children and beyond

Abstract: Air pollution (indoor and outdoor air) is a major issue in public health as epidemiological studies haven pointed to the numerous detrimental health consequences (notably, respiratory and cardiovascular pathology). In the last fifteen years, air pollution has also been considered as a potent environmental risk factor for neurological diseases and neuropathology. In this review, the authors examine the impact of air pollution on children's brain development and its clinical, cognitive, brain structural and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(119 citation statements)
references
References 111 publications
(115 reference statements)
1
115
0
3
Order By: Relevance
“…PM2.5 is currently a ubiquitous environmental pollutant, produced mainly by road traffic and industrial activities, and consists of diverse chemicals, including elemental carbon, minerals, metals, organic compounds, and biological compounds (Kim, Kabir, & Kabir, ). PM2.5 has been linked to elevated risk of respiratory and cardiovascular disease, neurological disorders, and reproductive function impairments (Calderón‐Garcidueñas, Leray, Heydarpour, Torres‐Jardón, & Reis, ; Sinharay et al, ; Xue & Zhu, ). Further, PM2.5 exposure during early life leads to developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…PM2.5 is currently a ubiquitous environmental pollutant, produced mainly by road traffic and industrial activities, and consists of diverse chemicals, including elemental carbon, minerals, metals, organic compounds, and biological compounds (Kim, Kabir, & Kabir, ). PM2.5 has been linked to elevated risk of respiratory and cardiovascular disease, neurological disorders, and reproductive function impairments (Calderón‐Garcidueñas, Leray, Heydarpour, Torres‐Jardón, & Reis, ; Sinharay et al, ; Xue & Zhu, ). Further, PM2.5 exposure during early life leads to developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse neuroinflammation, damage to the neuro-vascular unit, and the production of autoantibodies to neural and tight-junction proteins are worrisome findings in children chronically exposed to concentrations above the current standards for ozone and fine particulate matter (PM 2.5 ), and may constitute significant risk factors for the development of Alzheimer's disease later in life. Early cognitive deficits are associated with prenatal and early postnatal air pollutant exposures, and brain structural, volumetric and metabolic changes have been described in adolescence and early adulthood with significant cognitive deficits that have negative impacts on the academic, job-related and social performances of affected individuals [2].…”
Section: Introductionmentioning
confidence: 99%
“…[44] These particles have been shown to be composed of both organic and inorganic compounds, such as sulfates, nitrates, carbon, and ammonium, and various toxic metals, including mercury, cadmium, lead, tin, aluminum, and fluoride. Of particular importance, it has been shown that humans are frequently exposed to LPS suspended in the air as fine particles as part of house dust and dust from biosolids—a treated sewage sludge used for landscaping that contains a considerable amount of organic material, including bacterial components.…”
Section: Part IImentioning
confidence: 99%